Endoscopic management of common bile duct stones: European Society of Gastrointestinal Endoscopy (ESGE) guideline - Manes, Gianpiero; Paspatis, Gregorios; Aabakken, Lars; Anderloni, Andrea; Arvanitakis, Marianna; Ah-Soune, Philippe; Barthet, Marc; Domagk, Dirk; Dumonceau, Jean-Marc; Gigot, Jean-Francois; Hritz, Istvan; Karamanolis, George; Laghi, Andrea; Mariani, Alberto; Paraskeva, Konstantina; Pohl, Jürgen; Ponchon, Thierry; Swahn, Fredrik; ter Steege, Rinze W. F.; Tringali, Andrea; Vezakis, Antonios; Williams, Earl J.; van Hooft, Jeanin E. (Endoscopy, 2019)
ESGE recommends offering stone extraction to all patients with common bile duct stones, symptomatic or not, who are fit enough to tolerate the intervention.Strong recommendation, low quality evidence.ESGE recommends liver function tests and abdominal ultrasonography as the initial diagnostic steps for suspected common bile duct stones. Combining these tests defines the probability of having common bile duct stones.Strong recommendation, moderate quality evidence.ESGE recommends endoscopic ultrasonography or magnetic resonance cholangiopancreatography to diagnose common bile duct stones in patients with persistent clinical suspicion but insufficient evidence of stones on abdominal ultrasonography.Strong recommendation, moderate quality evidence.ESGE recommends the following timing for biliary drainage, preferably endoscopic, in patients with acute cholangitis, classified according to the 2018 revision of the Tokyo Guidelines:– severe, as soon as possible and within 12 hours for patients with septic shock– moderate, within 48 – 72 hours– mild, elective.Strong recommendation, low quality evidence.ESGE recommends endoscopic placement of a temporary biliary plastic stent in patients with irretrievable biliary stones that warrant biliary drainage.Strong recommendation, moderate quality of evidence.ESGE recommends limited sphincterotomy combined with endoscopic papillary large-balloon dilation as the first-line approach to remove difficult common bile duct stones. Strong recommendation, high quality evidence.ESGE recommends the use of cholangioscopy-assisted intraluminal lithotripsy (electrohydraulic or laser) as an effective and safe treatment of difficult bile duct stones.Strong recommendation, moderate quality evidence.ESGE recommends performing a laparoscopic cholecystectomy within 2 weeks from ERCP for patients treated for choledocholithiasis to reduce the conversion rate and the risk of recurrent biliary events. Strong recommendation, moderate quality evidence.